The Impact of Spatial Changes of Wetlands on Bio-Diversity: A Geo-Spatial Study on Tanguar Haor- Ramsar Site, Bangladesh - Nur Hussain; Islam MD Hasibul (Center for Journal Management and Publication, 2017)
Bangladesh is the largest delta in the world. Geographical location and seasonal diversity have made this country unique. Tanguar Haor as a Ramsar site is famous throughout the world with a reservoir of aquatic biodiversity. Due to availability of water flow throughout the year it has reached biodiversity compared to other haors in Bangladesh. In every winter, this haor becomes sonorous with the presence of thousands of migratory and resident birds. A lot of aquatic plants are floating and some are submerged. These aquatic plants decompose with seasonal shift and make the soil fertile. Numerous organism with food and shelter provided by these aquatic plants. Various species of amphibians and reptiles can also be seen in this vast haor. It has merged with the life and tradition of local people. Also human habitation has increased around the haor since the middle of the last century. About 12,870 ha water body have lost from 23,230 ha during last 60 years. Per year, 1.17% of water body have been lost in Tanguar Haor from 1955 to 2015. As a result, population of birds and wildlife is decreasing alarmingly due to the disturbance in the natural balance of the wetland ecosystem.